Plant growth-promoting properties of Streptomyces spp. isolates and their impact on mung bean plantlets’ rhizosphere microbiome - Nonthakaew, Napawit; Panbangred, Watanalai; Songnuan, Wisuwat; Intra, Bungonsiri (Frontiers in Microbiology, 2022)
Phytophthora is an important, highly destructive pathogen of many plants, which causes considerable crop loss, especially durians in Thailand. In this study, we selectively isolated Streptomyces from the rhizosphere soil with a potent anti-oomycete activity against Phytophthora palmivora CbP03. Two strains (SNN087 and SNN289) demonstrated exceptional plant growth-promoting properties in pot experiment. Both strains promoted mung bean (Vigna radiate) growth effectively in both sterile and non-sterile soils. Metagenomic analysis revealed that Streptomyces sp. SNN289 may modify the rhizosphere microbial communities, especially promoting microbes beneficial for plant growth. The relative abundance of bacterial genera Bacillus, Sphingomonas, Arthrobacter, and Pseudarthrobacter, and fungal genera Coprinellus and Chaetomium were noticeably increased, whereas a genus Fusarium was slightly reduced. Interestingly, Streptomyces sp. SNN289 exhibited an exploratory growth, which allows it to survive in a highly competitive environment. Based on whole genome sequence analysis combined with an ANI and dDDH values, this strain should be classifiable as a new species. Functional annotation was also used to characterize plant-beneficial genes in SNN087 and SNN289 genomes for production of siderophores, 3-indole acetic acid (IAA), ammonia, and solubilized phosphate. AntiSMASH genome analysis and preliminary annotation revealed biosynthetic gene clusters with possible secondary metabolites. These findings emphasize the potential for application of strain SNN289 as a bioinoculant for sustainable agricultural practice.